Measuring inclusive education - Loreman, Tim.; Forlin, Chris (Bingley, U.K. : Emerald, 2014)
In the first section, broad issues associated with assessment for, of, and in learning in inclusive classrooms; measuring the implementation of inclusive policy; identifying and removing barriers to inclusion; resourcing and financing; and, evaluating effective teacher preparation for inclusion provide the structure for discussion. The second section commences with a current and in-depth review of the literature on the development of international indicators for measuring inclusive education. Examples of some of the models presently employed to frame an evaluation of inclusive practice are studied. These provide illustrations of effective measurement strategies to evaluate inclusive educational practice at all levels of administration, from governments to classrooms, and ways to recognize the positive outcomes attained by all involved.
Conceptualising and measuring inclusive education / Tim Loreman ... [et al.] -- Ethical challenges and dilemmas in measuring inclusive education / Agnes Gajewski -- What is effective inclusion? Interpreting and evaluating a Western concept in an Indian context / Richard Rose ... [et al.] -- Data collection to inform international policy issues on inclusive education / Amanda Watkins, Serge Ebersold, András Lénárt -- Resourcing inclusive education / Donna Barrett -- Measuring effective teacher preparation for inclusion / Sarah Copfer, Jacqueline Specht -- Leading inclusive education : measuring 'effective' leadership for inclusive education through a Bourdieuian lens / Joseph S. Agbenyega, Umesh Sharma -- Identifying effective teaching practices in inclusive classrooms / Anne Jordan, Donna McGhie-Richmond -- Measuring indicators of inclusive education : a systematic review of the literature / Tim Loreman, Chris Forlin, Umesh Sharma -- Learning about inclusion from developing countries : using the index for inclusion / Suzanne Carrington, Jennie Duke -- Using networking to measure the promotion of inclusive education in developing countries : the case of the Pacific region / Susie Miles, Laisiasa Merumeru, Donna Lene -- School and classroom indicators of inclusive education / Julie Lancaster -- Assessing teacher competencies for inclusive settings : comparative pre-service teacher preparation programs / Kymberly Drawdy, Meng Deng, Catherine Howerter -- Developing and using a framework for gauging the use of inclusive pedagogy by new and experienced teachers / Lani Florian, Jennifer Spratt -- Using graduation rates of students with disabilities as an indicator of successful inclusive education / Janet I. Goodman ... [et al.].
Includes index.
Print version record
Keywords: Education -- Inclusive Education; Education -- General; Education -- Administration -- General; Inclusive education -- Mainstreaming; Schools; Inclusive education